2023
DOI: 10.1021/acscatal.3c01444
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobicity-Enabled Efficient Electrocatalytic CO2 Reduction at a High Temperature

Kaixin Li,
Siyu Zou,
Jun Zhang
et al.

Abstract: Enhancing the electrocatalytic CO2 reduction reaction (CO2RR) by a temperature increase is very attractive, but lower CO2 solubility and the more intense competitive hydrogen evolution reaction limit the practical implementation. Herein, we report an efficient CO2RR at relatively high temperatures using a superhydrophobic electrode with a solid–liquid–gas three-phase interface microenvironment. Based on the three-phase electrode, the partial current density of the reduction product CO was increased by 240% fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The high CO 2 concentration and fast CO 2 diffusion rate in the reaction region determine the performance of CO 2 RR. [111] In addition, the reaction temperature also affects the selectivity of CO 2 RR. [112] Koper et al investigated the product distribution at different temperatures and found that the products of electrocatalytic reduction at copper electrodes at temperatures ranging from 18 to 48 °C were mainly C 2 + products and hydrogen (Figure 9d).…”
Section: Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…The high CO 2 concentration and fast CO 2 diffusion rate in the reaction region determine the performance of CO 2 RR. [111] In addition, the reaction temperature also affects the selectivity of CO 2 RR. [112] Koper et al investigated the product distribution at different temperatures and found that the products of electrocatalytic reduction at copper electrodes at temperatures ranging from 18 to 48 °C were mainly C 2 + products and hydrogen (Figure 9d).…”
Section: Temperaturementioning
confidence: 99%
“…It is noteworthy that both partial current densities and turn‐over frequencies (TOFs) of the reduced product CO were significantly increased when the reaction temperature was increased (Figure 9c). The high CO 2 concentration and fast CO 2 diffusion rate in the reaction region determine the performance of CO 2 RR [111] . In addition, the reaction temperature also affects the selectivity of CO 2 RR [112] .…”
Section: Impact Of Environmental Conditionsmentioning
confidence: 99%
“…To address the above issues, it is effective to engineer TM@NC catalysts on a gas-diffusion layer (GDL) to fabricate a useful gas-diffusion electrode (GDE) in the flow cells and membrane electrode assemblies. , This approach eliminates the gas transport limitation by directly delivering the CO 2 gas to the triphasic reaction interfaces, thereby pushing the eCO 2 RR to achieve industrially relevant current densities. Unfortunately, many TMs@NC catalysts are prepared in a fine powder form, which necessitates the use of binders to adhere the catalyst powder onto the GDL.…”
Section: Introductionmentioning
confidence: 99%
“…It is believed that the hydrophobic backbones or pores within these additives or polymers trap more CO 2 near the catalyst surface and repeal water, thereby regulating local CO 2 and H 2 O concentrations 37 , 38 . This regulation subsequently results in increased current density and selectivity towards CO 2 R products 34 , 38 , 39 . However, it is challenging to attribute this enhancement solely to hydrophobicity, considering other factors such as polymer porosity or catalyst morphology, and valence state changes induced by the introduced polymer.…”
Section: Introductionmentioning
confidence: 99%